Thymoquinone ameliorates Pachycondyla sennaarensis venom-induced acute toxic shock in male rats - Alhazza, Ibrahim M. (BMC Pharmacol Toxicol, 2019)
BACKGROUND: For many decades, the sting of Samsun ant (Pachycondyla sennaarensis) has been a serious clinical challenge for the people living in some of the major Middle East and Asian countries. In the present study, the therapeutic potential of Nigella sativa derived plant extract component, thymoquinone (TQ) has been tested against the Samsun ant venom (SAV) at the toxic dose in the rats. METHODS: The adult male rats were divided into four groups (n = 10): control, SAV treated, SAV + TQ treated and TQ alone treated. It was found that the sub-lethal dose of SAV alters not only many of the kidney and liver function markers but also induces oxidative stress in the animals. Moreover, the SAV also disturbs various immunological parameters including expression of PMNs, CD-80, CD-86, interleukins and other cytokines compromising the affected organism towards mild to severe allergic reactions including life-risking anaphylaxis. RESULTS: The plant extract, TQ, effectively restores many of the biochemical and oxidative stress parameters comparable to the normal concomitant with improving the immunological aspects that might attributive in relieving from SAV-induced toxicity and allergic reactions in the affected organism to a greater extent. CONCLUSION: Hence, TQ has an excellent antidote property against SAV-induced toxicities in vivo. Although the study is a vivid indication of the potential therapeutic potential of TQ against the SAV induced in vivo toxicity, yet the actual mechanism of interaction translating the toxicity amelioration warrants further investigations.